SLOVENSKI JEZIK NA STIČIŠČU VEČ KULTUR. Ur. Marko Jesenšek: Maribor: Filozofska fakulteta, Mednarodna založba Oddelka za slovanske jezike in književnosti (Zora; 102). 378 str. - Rezar, Cvetka (Slavia Centralis, 2020)
The article presents the monograph Slovene language at the crossroads of several cultures, published in 2014 in the international book collection Zora (Zora 102, editor Marko Jesenšek).
Keywords: Slovenski jezik na stičišču več kultur; Slovene language at the crossroads of several cultures; monograph; Zora; review; Slovene language